Mechanistic Studies of Antibody-Mediated Clearance of Tau Aggregates Using an ex vivo Brain Slice Model - Krishnamurthy, Pavan; Deng, Yan; Sigurdsson, Einar M. (Frontiers in Psychiatry, 2011)
Recent studies have shown that immunotherapy clears amyloid beta (A) plaques and reduces A levels in mouse models of Alzheimer’s disease (AD), as well as in AD patients. Tangle pathology is also relevant for the neurodegeneration in AD, and our studies have shown that active immunization with an AD related phospho-tau peptide reduces aggregated tau within the brain and slows the progression of tauopathy-induced behavioural impairments. Thus, clearance of neurofibrillary tangles and/or their precursors may reduce synaptic and neuronal loss associated with AD and other tauopathies. So far the mechanisms involved in antibody-mediated clearance of tau pathology are yet to be elucidated. In this study we have used a mouse brain slice model to examine the uptake and localization of FITC labeled anti-tau antibodies. Confocal microscopy analysis showed that the FITC labelled anti-tau antibody co-stained with phosphorylated tau, had a perinuclear appearance and co-localised with markers of the endosomal/lysosomal pathway. Additionally, tau and FITC IgG were found together in an enriched lysosome fraction. In summary, antibody-mediated clearance of intracellular tau aggregates appears to occur via the lysosomal pathway.